KOPI RAKYAT: INVESTASI IBADAH HAJI MASYARAKAT DESA MULYOREJO KECAMATAN SILO KABUPATEN JEMBER - Latifatul Izzah (LITERASI: Indonesian Journal of Humanities, 2015)
This article discusses the condition of the community in Mulyorejo village, Silo subdistrict, Jember regency that is discredited by the government of Jember regency and categorized as a poor village. Through the poverty theory and from primary and secondary sources, this research can prove a contrary reality about the community. Almost 70 percent of the community invests their money for pilgrimage to Mecca. Their economic sources depend on the harvest of the traditional Coffee Plantations owned by the local farmers. The natural condition of the village as a rural area causing the village community do not have a sufficient facility for health and electricity from the government. However, these conditions do not make the villagers frustrated, but encourage them to establish a micro-hydro power plant using self-generated funds. The efforts to get the power plant they have done is a long-term infestation that earns billions of Rupiah.Keywords: smallholder coffee, haj investment, Mulyorejo district community